Parapharyngeal tuberculoid mass: A rare complication of Bacillus Calmette‐Guérin therapy for urothelial carcinoma in situ - Karolina A. Plonowska‐Hirschfeld; Monica Fung; Christine Glastonbury; Patrick K. Ha (Clinical Case Reports, 2021)
Key Clinical Message Local and systemic complications of Bacillus Calmette‐Guérin therapy are important to recognize as they require prolonged antimicrobial therapy; molecular genomic testing may be key to diagnosis when culture data are inconclusive.